Altered Volume and Functional Connectivity of the Habenula in Schizophrenia - Zhang, Lei; Wang, Hao; Luan, Shuxin; Yang, Shaojun; Wang, Zhuo; Wang, Jinhui; Zhao, Hua (Frontiers in Human Neuroscience, 2017)
The pathogenesis of schizophrenia is associated with the dysfunction of monoamine neurotransmitters, the synthesis and release of which are mainly regulated by a key structure, the habenular nucleus (Hb). However, little is known regarding whether schizophrenia is associated with structural or functional alterations in the Hb. In this study, we combined structural and resting-state functional magnetic resonance imaging to investigate the changes in volume and functional connectivity of the Hb in 15 patients with schizophrenia (SCH) versus 16 age- and gender-matched healthy controls (HCs). Morphologically, the absolute volume of the bilateral Hb was significantly lower in the SCH patients than in the HCs. Functionally, the bilateral Hb showed significantly enhanced functional connectivity with the left medial prefrontal cortex (mPFC) in the SCH patients. Additionally, the SCH patients exhibited increased functional connectivity of the left Hb with the left lingual gyrus and right inferior frontal gyrus. A further exploratory analysis revealed that the SCH patients showed increased functional connectivity between the right Hb and several subcortical regions related to dopaminergic pathways, including the left ventral striatum, caudate and putamen. Finally, the increased functional connectivity of the right Hb with the mPFC was positively correlated with the Brief Psychiatric Rating Scalescores in the patients. Together, these results suggest that the altered volume and functional connectivity of the Hb may be involved in the pathogenesis of schizophrenia and thus that the Hb may serve as a potential target in developing new therapeutic strategies in schizophrenia.